2004
DOI: 10.1086/423174
|View full text |Cite
|
Sign up to set email alerts
|

On the Spatial Dependence of Low-Degree Solar p -Mode Frequency Shifts from Full-Disk and Resolved-Sun Observations

Abstract: We have analyzed low angular degree (low-) solar p-mode frequency shifts extracted from two types of ᐉ observations, both made by instruments on board the ESA/NASA Solar and Heliospheric Observatory satellite during a period that covers the rising phase of activity, cycle 23 (1995-2002). The first are full-disk (Sun-as-astar) averages made in Doppler velocity by the Global Oscillations at Low Frequency spectrophotometer; the second are Doppler velocity observations made with high spatial resolution by the Mich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 5 publications
3
32
0
Order By: Relevance
“…Jiménez-Reyes et al (2004) previously showed that the values of the frequency shifts for l = 0, 1, and 2 measured in MDI data scale to the corresponding spherical harmonic components of the observed lineof-sight surface magnetic field. The analysis of the variability in the other p-mode parameters during this extended minimum is also currently underway.…”
Section: Summary and Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…Jiménez-Reyes et al (2004) previously showed that the values of the frequency shifts for l = 0, 1, and 2 measured in MDI data scale to the corresponding spherical harmonic components of the observed lineof-sight surface magnetic field. The analysis of the variability in the other p-mode parameters during this extended minimum is also currently underway.…”
Section: Summary and Discussionmentioning
confidence: 80%
“…A marginal but significant l dependence of the frequency shifts of the low-degree p modes has also been clearly identified (Jiménez-Reyes et al 2004;Chaplin et al 2004). The size of the shift also reflects differences in mode inertia.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations